2021
DOI: 10.3390/vaccines9101174
|View full text |Cite
|
Sign up to set email alerts
|

Course and Lethality of SARS-CoV-2 Epidemic in Nursing Homes after Vaccination in Florence, Italy

Abstract: Evidence on the effectiveness of SARS-CoV2 vaccines in nursing home (NHs) residents is limited. We examined the impact of the BNT162b2 mRNA SARS-CoV2 vaccine on the course of the epidemic in NHs in the Florence Health District, Italy, before and after vaccination. Moreover, we assessed survival and hospitalization by vaccination status in SARS-CoV2-positive cases occurring during the post-vaccination period. We calculated the weekly infection rates during the pre-vaccination (1 October–26 December 2020) and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 23 publications
7
37
0
Order By: Relevance
“…Yet, hospitalization rate (8%) significantly increased as compared to the early post‐vaccination period (3%), 15 getting closer to that reported in unvaccinated residents during the second wave (10%) 17 . Lethality rate (8%) was significant, but lower than previously reported in unvaccinated residents of the study area (23%) 17 and similar to that observed in the early post‐vaccination period (6%) 15 . Lethality was consistent with what was recently described in a smaller sample of NH residents during a Spanish post‐vaccination outbreak, 20 while hospitalization rate was lower, possibly due to the “hospital‐at‐nursing home” model of care that has been adopted by the Florence Health District during COVID‐19 epidemic 17 …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Yet, hospitalization rate (8%) significantly increased as compared to the early post‐vaccination period (3%), 15 getting closer to that reported in unvaccinated residents during the second wave (10%) 17 . Lethality rate (8%) was significant, but lower than previously reported in unvaccinated residents of the study area (23%) 17 and similar to that observed in the early post‐vaccination period (6%) 15 . Lethality was consistent with what was recently described in a smaller sample of NH residents during a Spanish post‐vaccination outbreak, 20 while hospitalization rate was lower, possibly due to the “hospital‐at‐nursing home” model of care that has been adopted by the Florence Health District during COVID‐19 epidemic 17 …”
Section: Discussionmentioning
confidence: 97%
“…This primary vaccination course, together with strict prevention measures, was associated with a sharp decline in SARS-CoV-2 new cases among NH residents over the following 2 months, with infection rate falling to zero by March 2021, as described in a previous paper. 15 In the present study, we enrolled residents living in Florence NHs as of April 1st 2021, and we calculated the weekly breakthrough infection rates for 7 months, until…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the extent of vaccination coverage, local prevalence of infection, and necessity of the contact should be carefully considered before allowing any gathering of individuals. Even in high-risk individuals such as those in care homes, SARS-CoV-2 vaccination has been associated with significant reductions in infection rates, and significantly lower risk of morbidity and mortality following SARS-CoV-2 infection compared with those seen pre-vaccination [ 119 , 120 ].…”
Section: Different Testing Settingsmentioning
confidence: 99%